MANAJEMEN KURIKULUM INTEGRASI DI MADRASAH TSNAWIYAH NEGERI 2 KOTA MALANG - Wahyudi Widodo (Leadership: Jurnal Mahasiswa Manajemen Pendidikan Islam, 2021)
Integration curriculum management is an effort to explain all components that combine general science and religious science in achieving Islamic educational goals without any dichotomy of science. The curriculum in that question is a curriculum that strengthens monotheism, with the intention of describing Islam which complete, comprehensive and integral.        This research was conducted at MTsN 2 Kota Malang  that are advanced and performing with the aim of analyzing and finding: (1) the concept of integration curriculum, (2) implementation of integration curriculum management, (3) implications of integration curriculum management.         This study uses an interpretative paradigm, with a qualitative approach, a type of case study, with a multi site design. Data collection is done by in-depth interviews, participant observation, and documentation.            The formal finding of this research is Curriculum Management Based Spiritual